Perfectionism in football - Araki, K. (7th World Congress on Science and Football (WCSF), 2011, 2011)
The purpose of the presentation is to share the knowledge on perfectionism in sport as well as applications of the knowledge in football. Perfectionism research in counseling and clinical psychology has been developed last 20 years. Some sport psychology researchers also started to find perfectionistic tendency among athletes. How the perfectionistic tendency may affect athletes` performance and enjoyment in sport will be presented.